Hermite-Hadamard-Type Inequalities for r-Preinvex Functions - Wasim Ul-Haq; Javed Iqbal (Journal of Applied Mathematics)
We aim to find Hermite-Hadamard inequality for r-preinvex functions. Also, it is investigated for the product of an r-preinvex function and s-preinvex function.